Reconciling copyright with cumulative creativity : the third paradigm - Frosio, Giancarlo F. (CEIPI studies in intellectual property, 2018)
Reconciling Copyright with Cumulative Creativity: The Third Paradigm examines the long history of creativity, from cave art to digital remix, in order to demonstrate a consistent disparity between the traditional cumulative mechanics of creativity and modern copyright policies. From Platonic mimesis to Shakespeare's 'borrowed feathers', culture was produced under a paradigm in which imitation, plagiarism, and social authorship formed key elements of the creative moment (the 1st paradigm). However, the cumulative nature of creativity is rarely accounted for in modern copyright policies, which build upon a post-Romantic individualistic view emphasizing absolute originality rather than imitation (the 2nd paradigm). Today, in an era of networked mass collaboration and user-based creativity, the enclosure of knowledge brought about by an ever-expanding copyright paradigm seems archaic, and a deliberate defiance of inevitable cultural evolution. Giancarlo Frosio calls for returning creativity to an inclusive rather than exclusive process, so that the 1st and 2nd creative paradigms can be reconciled into an emerging third paradigm. This ground-breaking work will appeal to those interested in both the history and future of creativity and copyright.